Management of patients with hereditary angioedema in Germany: comparison with other countries in the Icatibant Outcome Survey. (23rd October 2018) - Maurer, M.; Bork, K.; Martinez‐Saguer, I.; Aygören‐Pürsün, E.; Botha, J.; Andresen, I.; Magerl, M.
Abstract: Background: The Icatibant Outcome Survey (IOS; NCT01034969) is a Shire‐sponsored, international, observational study monitoring the safety and effectiveness of icatibant, a bradykinin B2 receptor antagonist approved for the acute treatment of adults with hereditary angioedema with C1 inhibitor deficiency (HAE‐C1‐INH). Objective: To report IOS data comparing demographic and icatibant treatment outcomes in patients with HAE‐C1‐INH from Germany to HAE‐C1‐INH patients from 11 other IOS countries. Methods: A descriptive, retrospective, comparative analysis of data from 685 IOS patients with HAE‐C1‐INH from seven centres in Germany ( n  =   93) vs. centres from Austria, Brazil, Czech Republic, Denmark, France, Greece, Israel, Italy, Spain, Sweden and the United Kingdom ( n  =   592, July 2009–January 2017). Icatibant treatment outcomes were retrieved from patients with complete attack outcome data for time to treatment, time to resolution and attack duration (160 attacks in 42 German patients and 1442 attacks in 251 patients from other IOS countries). Results: German patients reported significantly fewer severe/very severe attacks (38.7% vs. 57.5%, respectively; P  <   0.001). The proportion of attacks treated with a single icatibant injection was significantly higher in German patients (97.1% vs. 91.6%, P  =   0.0003). The median time to treatment (0.0 h vs. 1.5 h), time to resolution (3.0 h vs. 7.0 h) and attack duration (4.3 h vs. 10.5 h) in German patients vs. other IOS countries were all significantly shorter (all P  <   0.0001). No meaningful differences were identified between patients from Germany and other countries with regard to sex, median age at enrolment, median age at symptom onset and median age at diagnosis. Conclusion: German IOS patients share similar demographic characteristics to patients from other IOS countries yet treat their attacks with icatibant significantly earlier and have markedly fewer severe or very severe attacks. Factors including regional access to and availability of icatibant may drive these outcomes and warrant further investigation.